2014
DOI: 10.5123/s1679-49742014000300009
|View full text |Cite
|
Sign up to set email alerts
|

Perfil das internações por condições sensíveis à atenção primária em Pernambuco, 2008 a 2012

Abstract: Objetivo: descrever o perfil das internações por condições sensíveis à atenção primária (ICSAP) no estado de Pernambuco, no período de 2008 a 2012. Métodos: estudo descritivo com dados do Sistema de Informações Hospitalares do Sistema Único de Saúde (SIH/SUS), referentes a residentes no estado; foram calculados a proporção, o coeficiente e a variação percentual das ICSAP por região de saúde. Resultados: 20,0% das internações ocorridas em Pernambuco (n=559.975) foram por ICSAP, com redução no período estudado (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
12

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 15 publications
1
10
0
12
Order By: Relevance
“…19 Some studies have pointed to a significant inverse correlation between increased FHS coverage and a reduction in rates of HCSPCs in the adult population. [14][15][16][17] However, this relation has not been reported consistently in other studies and each Brazilian State has its own peculiarities. 20 A study in the south of Minas Gerais found the rates for two time periods to behave differently for different age groups.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…19 Some studies have pointed to a significant inverse correlation between increased FHS coverage and a reduction in rates of HCSPCs in the adult population. [14][15][16][17] However, this relation has not been reported consistently in other studies and each Brazilian State has its own peculiarities. 20 A study in the south of Minas Gerais found the rates for two time periods to behave differently for different age groups.…”
Section: Discussionmentioning
confidence: 78%
“…9,14-16 However, it is important to note that the studies that evaluated the pattern of hospitalizations in adult patients found a more marked drop in HCSPC rates. [14][15][16][17] For the population studied, it was found that, in fact, there was a tendency for all rates to decline, but this was clearest only in the last four years of the series. A similar finding appeared in a study conducted in the State of Pernambuco, for the period between 1999 and 2009, in a population of children aged under five years, in which almost half of hospitalizations were attributed to conditions susceptible to primary care.…”
Section: Discussionmentioning
confidence: 90%
“…Na Segunda Regional de Saúde do Paraná, a análise de ICSAP em adolescentes durante cinco anos, destacam-se que os cinco diagnósticos mais frequentes de ICSAP no cenário e população deste estudoconvergem com outras pesquisas realizadas no Brasil, com faixas etárias e recortes temporais semelhantes (20)(21) .…”
Section: Discussionunclassified
“…O declínio dos valores desse indicador de qualidade de assistência à saúde com foco na atenção primária acompanha os estudos realizados no Brasil e no mundo, além de sugerir que a lista brasileira contém condições que de fato podem ser tratadas nesse nível de atenção, prevenindo agravos que geram internações [12][13][14][15][16] . Destaca-se, nessa direção, a redução de 38,1% na cidade de Florianópolis em um período um pouco menor, de 2005 a 2011, no qual ocorreu o mesmo movimento de expansão da APS, indo de 61,7 a 89,3% de cobertura de ESF no período analisado e chegando a 100% de cobertura no ano de 2015 16 .…”
Section: ▄ Discussãounclassified